2018
DOI: 10.1136/tobaccocontrol-2018-054433
|View full text |Cite
|
Sign up to set email alerts
|

Invisible smoke: third-party endorsement and the resurrection of heat-not-burn tobacco products

Abstract: BackgroundTobacco companies are introducing new ‘heat-not-burn’ cigarettes in dozens of countries. Historically, these products failed commercially, and independent researchers contested their health claims. The most prominent early heat-not-burn cigarette was RJ Reynolds’s (RJR’s) Premier, introduced in the USA in 1988. Curiously, The Lancet endorsed Premier as a ‘near-perfect low tar cigarette’ in a 1991 editorial, 2 years after Premier had been removed from the market. We examined the context of this endors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…Tobacco companies have designed sophisticated marketing strategies for HTPs, and many smokers are exposed to advertisements purporting that HTPs can replace combustible cigarettes [ 27 ]. However, the results of the present study suggested that a complete replacement of combustible cigarettes with HTPs was unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco companies have designed sophisticated marketing strategies for HTPs, and many smokers are exposed to advertisements purporting that HTPs can replace combustible cigarettes [ 27 ]. However, the results of the present study suggested that a complete replacement of combustible cigarettes with HTPs was unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the past decade and a half, the tobacco industry became a vocal proponent of tobacco harm reduction and has invested millions of US dollars in research and development of new products, such as HTP, which the tobacco industry is now using to gain access to scientists, opinion leaders and decision makers as a ‘solution’ to address the tobacco epidemic. Elias and Ling 89 describe the role the tobacco industry played a role in funding the earliest efforts to promote ‘clean nicotine’ for harm reduction and conclude that the tobacco industry will continue to seek endorsement from health authorities to its proposition of HTP as a ‘harm reduction’ strategy.…”
Section: Discussionmentioning
confidence: 99%
“…All these activities have the potential to change social norms and attitudes towards tobacco use, and suggest to the public that HTPs are a safe form of tobacco use. Elias and Ling emphasized the key role of respected health leaders in shaping public attitudes towards novel tobacco products and their impact on the commercial fate of HTPs [97]. The authors encouraged public health experts to carefully formulate opinions, bearing in mind the past experience with the industry-backed "safer tobacco products," such as filtered and low-tar cigarettes, which served to undermine and delay the global tobacco control efforts [97].…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 99%
“…Elias and Ling emphasized the key role of respected health leaders in shaping public attitudes towards novel tobacco products and their impact on the commercial fate of HTPs [97]. The authors encouraged public health experts to carefully formulate opinions, bearing in mind the past experience with the industry-backed "safer tobacco products," such as filtered and low-tar cigarettes, which served to undermine and delay the global tobacco control efforts [97]. Lempert and Glantz pointed out legal uncertainties regarding HTPs, especially electronic devices used to heat up tobacco sticks [98].…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 99%